A problematic paradox - Sappingfield, Eliot (New York, NY : G. P. Putnam's Sons, 2018)
Thirteen-year-old Nikola Kross's world is turned upside down when her father is abducted by aliens and she is suddenly transported to a special boarding school for geniuses, but things get even stranger when she realizes she has certain abilities that put her entire school in grave danger.
Keywords: Genius -- Fiction; Extraterrestrial beings -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Science fiction